Kedudukan Dan Sanksi Saksi Yang Memberikan Keterangan Palsu Dalam Perspektif Hukum Pidana Islam Dan Hukum Positif Indonesia - Ramdani, Rahmat Memo; Nashriana, Nashriana; Febriansyah, Artha (Consensus : Jurnal Ilmu Hukum, 2026)
Witness testimony is a crucial element in uncovering material truth in criminal proceedings. However, the practice of providing false testimony under oath remains a serious challenge that undermines the integrity of the justice system and obstructs the achievement of justice. This study analyzes the legal position of witnesses and compares sanctions for false testimony from the perspectives of Indonesian Positive Law and Islamic Criminal Law. The research employs a qualitative method with normative-juridical and comparative approaches through literature review. The findings indicate that under Indonesian Positive Law, witnesses are recognized as primary procedural evidence regulated by the Criminal Procedure Code (KUHAP), and providing false testimony is punishable by seven to nine years of imprisonment (Article 242 of the Criminal Code) as a form of obstruction of justice. In Islamic Criminal Law, testimony emphasizes the moral integrity (‘adalah) and piety of the witness; false testimony is classified as a major sin (kabirah) and jarimah ta’zir, with sanctions applied flexibly at the discretion of the judge or ruler to restore victims’ rights and social order. Both systems agree that false testimony harms public justice, yet Positive Law emphasizes formal-repressive aspects and secular legal certainty, whereas Islamic law integrates moral, religious-ethical dimensions and spiritual accountability before God. In conclusion, strengthening law enforcement mechanisms and raising witnesses’ legal awareness are essential to ensure a dignified and transparent justice system.